Sex as a moralistic turn in the film adaptation of The Wings of the Dove - Costa, Cynthia Beatrice (Letras, 2025)
Sex, in act and idea, is vastly present in the work of Henry James. In the novel The Wings of the Dove, sexual intercourse is used as a bargaining currency between the protagonists. Its 1997 film adaptation, directed by Iain Softley, makes this exchange explicit, showing sex scenes where there were only suggestions in the book. This essay argues that the “explicitation” – a term borrowed from Translation Studies – of sex in the adaptation turns the film into more of a sentimental and moralistic narrative, in contrast with Jamesian modernism. By examining this hypothesis, it indicates that explicitation risks not only condemning a work to go from polysemy to monosemy, as warned by Antoine Berman, but to change its entire ethos.